Co-designing Infrastructures Community collaboration for liveable cities - Bell, Sarah (Engaging Communities in City-making, 2023)
Co-designing Infrastructures tells the story of a research programme designed to bring the power of engineering and technology into the hands of grassroots community groups, to create bottom-up solutions to global crises. Four projects in London are described in detail, exemplifying community collaboration with engineers, designers and scientists to enact urban change. The projects co-designed solutions to air pollution, housing, the water-energy-food nexus, and water management. Rich case-study accounts are underpinned by theories of participation, environmental politics and socio-technical systems. The projects at the heart of the book are grounded in specific settings facing challenges familiar to urban communities throughout the world. This place-based approach to infrastructure is of international relevance as a foundation for urban resilience and sustainability. The authors document the tools used to deliver this work, providing guidance for others who are working to deliver local technical solutions to complex social and environmental problems around the world. This is a book for engineers, designers, community organisers and researchers. Co-authored by researchers, it includes voices of community collaborators, their experiences, frustrations and aspirations. It explores useful theories about infrastructure, engineering and resilience from international academic research, and situates them in community-based co-design experience, to explain why bottom-up approaches are needed and how they might succeed.